1982
DOI: 10.1073/pnas.79.9.3028
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils are required for the DNA synthetic response of human lymphocytes to mevalonic acid: evidence suggesting that a nonsterol product of mevalonate is involved.

Abstract: Communicated by Leon 0. Jacobson, January 25, 1982 ABSTRACT Human peripheral blood lymphocytes, in the presence of human neutrophils, initiate DNA synthesis and cell cycling when exposed to mevalonic acid. The ability of lymphocytes to respond in this manner is a radiosensitive property of the cells, whereas the help provided by neutrophils is maintained despite their prior exposure to x-irradiation. Other organic acid anions, including precursors of mevalonic acid biosynthesis and a variety ofproducts ofme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
1
6
0
2
Order By: Relevance
“…2 ) . This degree of inhibition of sterol synthesis by mevinolin added to the glial primary cultures is comparable to the inhibition that has been reported with addition of analogous competitive inhibitors of HMG-CoA reductase to cultures of nonneural cell types (Brown et al, 1978;Kaneko et al, 1978;Habenicht et al, 1980;Heiniger and Marshall, 1982;Larson et al, 1982;Perkins et al, 1982;Quesney-Huneeus et al, 1983;Fairbanks et al, 1984) and C-6 glioma cells (Volpe and Obert, 1982;Bhat and Volpe, 1983).…”
Section: Inhibition Of Sterol Synthesis By Mevinolin Added At the Timsupporting
confidence: 73%
See 2 more Smart Citations
“…2 ) . This degree of inhibition of sterol synthesis by mevinolin added to the glial primary cultures is comparable to the inhibition that has been reported with addition of analogous competitive inhibitors of HMG-CoA reductase to cultures of nonneural cell types (Brown et al, 1978;Kaneko et al, 1978;Habenicht et al, 1980;Heiniger and Marshall, 1982;Larson et al, 1982;Perkins et al, 1982;Quesney-Huneeus et al, 1983;Fairbanks et al, 1984) and C-6 glioma cells (Volpe and Obert, 1982;Bhat and Volpe, 1983).…”
Section: Inhibition Of Sterol Synthesis By Mevinolin Added At the Timsupporting
confidence: 73%
“…Thus, after it was reported that DNA synthesis in mitogenically stimulated lymphocytes is prevented by inhibition of sterol synthesis (Chen et al, 1975), investigation of both cloned smooth muscle cells and fibroblasts demonstrated that inhibition of HMG-CoA reductase resulted in a growth arrest that was reversed when mevalonate, but not cholesterol, was added to the culture medium (Habenicht et al, 1980). Further studies of lymphocytes (Larson et al, 1982;Perkins et a]., 1982) also suggested that mevalonate, rather than cholesterol, is the critical intermediate required for the initiation of DNA synthesis. However, another study of stimulated lymphocytes indicated that cholesterol itself was sufficient to restore proliferation when sterol synthesis was inhibited (Heiniger and Marshall, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two patients were studied three times and four patients were studied twice and a significant mitogenic response to cytochalasin B was observed in each instance. In experiments with lymphocytes from 11 patients, the response to cytochalasin B exceeded that of the same cell suspension to either 50 jAg/ml Con A (six cases), 10 jig/ml PHA (six cases), or 0.5 jig/ml PWM (all 11 patients). With cells from eight patients the response to cytochalasin B exceeded that to 100 ng/ml PMA.…”
Section: Methodsmentioning
confidence: 99%
“…This agent suppresses the synthesis of mevalonic acid by competitively and reversibly inhibiting 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase, the enzyme required for conversion of HMG-CoA to mevalonic acid [11]. In addition to inhibition of mevalonate synthesis, Lovastatin or compactin, another fungal toxin [12], also inhibits DNA replication [13][14][15][16][17][18], DNA replication is restored by the addition of mevalonate, the product of the reaction catalyzed by HMG-CoA reductase.…”
Section: Introductionmentioning
confidence: 99%